1991
DOI: 10.1530/acta.0.1250359
|View full text |Cite
|
Sign up to set email alerts
|

Middle-aged women with Turner's syndrome. Medical status, hormonal treatment and social life

Abstract: A study of 49 middle-aged (>35 years old) women with Turner's syndrome was performed to evaluate medical status, hormonal treatment and social life. Most of the women lived a normal social life in stable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
3
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 8 publications
4
59
3
8
Order By: Relevance
“…One study found elevated levels of hepatic enzymes in 80% of middle-aged women with Turner syndrome, but could not associate the findings with overt hepatic disease (296). We found serum levels of alanine aminotransferase, g-glutamyl transferase, and total alkaline phosphatase to be higher in Turner patients compared with controls.…”
Section: Spontaneous Hepatic Functioncontrasting
confidence: 83%
See 1 more Smart Citation
“…One study found elevated levels of hepatic enzymes in 80% of middle-aged women with Turner syndrome, but could not associate the findings with overt hepatic disease (296). We found serum levels of alanine aminotransferase, g-glutamyl transferase, and total alkaline phosphatase to be higher in Turner patients compared with controls.…”
Section: Spontaneous Hepatic Functioncontrasting
confidence: 83%
“…How should a person with 5% (or less) 45,X cells and 95% 46,XX cells be considered, knowing that normally a karyotype is performed on Table 1 Detailed list of abnormalities associated with Turner syndrome with the tentative frequency of a specific abnormality given as a percentage. The table is compiled from different sources (8,55,178,296,305,307,321,350).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of thyroid abnormalities increases with age in Turner syndrome as well as in the general population. The incidence of hypothyroidism due to Hashimoto's thyroiditis in adults with Turner syndrome was reported as 16-30% [1,4,[7][8][9]. In 2005, el-mansoury et al reported that the prevalence of hypothyroidism in Swedish adults with Turner syndrome was 25% in a large cohort study [8].…”
Section: Resultsmentioning
confidence: 99%
“…Stature is short, and morbidity is increased due to risk of osteoporosis and fractures, type 2 diabetes, ischemic heart disease, hypertension, and stroke, but also the risk of cirrhosis is increased (1). Clinical studies have shown a frequent occurrence of elevated liver enzymes, primarily alanine aminotransferase (ALAT), g-glutamyl-transferase (gGT), and alkaline phosphatase (AP), while bilirubin is normal (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%